Dos sujeitos, dos medos e da espera: a construção social do Cólera-Morbus na província cearense (1855 – 1863) - Maciel, Dhenis Silva (2017)
In this work we sought to understand the cholera epidemic in the province of Ceará in the period between 1856 and 1863 and how it was seen, felt and interpreted by the individuals who lived in Ceará in this period. We observed, through the sources, the positioning of individuals who composed the medical, religious and provincial public administration. We sought to observe and analyze their actions in the face of the disease in these two distinct moments, since cholera presented itself in different forms to the people of Ceará. In 1856 the Brazilian authorities watched almost without power the devastating action of the cholera epidemic that, when it had recently arrived from Europe, made countless victims in all the ports where it passed. In Ceará, he was apprehensive because he had ventured into almost all the neighboring provinces: Pernambuco, Paraíba, Piauí and Bahia, it seemed only a matter of time before the cholera arrived. But he did not come. Faced with such a reality a discourse of belief in a proverbial healthiness reigned for little more than five years. In 1862 the plague was on its way again, but then, little was done. There was nothing to indicate that the disease would have a place in the lands of Ceará, but to the surprise of many, the epidemic came with force, in less than half a year it disrupted productive systems, media, motivated reordering of parishes and power in the province of Ceará. The same illness, two moments, two different realities. The central point of this thesis is the understanding of the distinct way in which the epidemic initially spread, using not the usual coastal-sertao path, but starting from the ox roads towards the coast. We have as main sources official documents such as Reports of Presidents of Province, Letters of Commissions of Public Relief, Documents sent by the head of the province to the minister marquis de Olinda, as well as hemerográficas sources (O Cearense, Pedro II, O Commercial and O Araripe) and chroniclers' accounts. We seek to read these documents, to focus on the social experiences that have been experienced and on the fears and hopes aroused by cholera, in order to try to glimpse the representations provoked by the harvesting of diverse human lives in a short time.